Composite-composite adhesion as a function of material and surface treatment - Ritter, André Vicente (2019)
The purpose of this study was to evaluate various surface treatment and adhesion strategy variables in the composite-to-composite repair bond strength. The intent was to focus on recently-introduced composites and adhesives, as well as both artificially aged composite and laboratory processed composite as the repair substrate. Study one evaluated the influence of composite resin type (nanohybrid vs. nanofill), adhesive type (self-etch 1-step vs. self-etch 2-step), and composite surface acid etching on the composite-to-composite repair adhesive strenght using a interfacial fracture toughness (iFT) test; a second study evalauted the influence of sandblasting and CoJet tribochemical treatment on the composite-to-composite repair adhesive strenght using iFT test; the third and last study evaluated the influence of CoJet tribochemical treatment and type of resin cement (adhesive vs. autoadhesive) on the microtensile bond strength of an indirect composite resin to dentin. Results showed that (1) regardless of the type of composite resin being repaired, and of the adhesive used, higher iFT means were obtained when the nanofill composite (Filtek Supreme Ultra) was used as the repair material; (2) 10-MDP based adhesives resulted in higher composite repair strengths when compared to negative controls (no adhesive); (3) acid etching of the composite surface being repaired has no influence on the repair strength; (4) tribochemical treatment with CoJet results in significantly higher composite-composite repair strengths; (5) tribochemical treatment with CoJet results in significantly higher microtensile bond strengths of the indirect composite Lava Ultimate to dentin; and (6) the adhesive resin cement (RelyX Ultimate) afforded higher microtensile bond strengths between the indirect composite resin (Lava Ultimate) and dentin when compared to the autoadhesive resin cement (RelyX Ultimate 2). Overall these studies show that composite-composite adhesion can be facilitated by 10-MDP-based adhesives and tribochemical surface treatment, and that iFT appears to be a suitable and reliable method to assess adhesion between composite materials. The findings lend support to composite-composite adhesion (and by extension composite repair) to minimize the impact of replacement of partially-failing restorations. This approach can lead to increased tooth longevity and better oral health outcomes for patients of all ages.